A National Survey on Public Perceptions of Miscarriage. Issue 6 (June 2015) - Bardos, Jonah; Hercz, Daniel; Friedenthal, Jenna; Missmer, Stacey A.; Williams, Zev
Abstract : OBJECTIVE: To assess attitudes and perceptions of U.S. survey respondents regarding prevalence, causes, and emotional effects of miscarriage. METHODS: We used a questionnaire consisting of 33 questions administered in January of 2013 to men and women aged 18–69 years across the United States. RESULTS: Participants from 49 states completed the questionnaire: 45% male and 55% female (N=1, 084). Fifteen percent reported they or their partner experienced at least one miscarriage. Fifty-five percent of respondents believed that miscarriage occurred in 5% or less of all pregnancies. Commonly believed causes of miscarriage included a stressful event (76%), lifting a heavy object (64%), previous use of an intrauterine device (28%), or oral contraceptives (22%). Of those who had a miscarriage, 37% felt they had lost a child, 47% felt guilty, 41% reported feeling that they had done something wrong, 41% felt alone, and 28% felt ashamed. Nineteen percent fewer people felt they had done something wrong when a cause for the miscarriage was found. Seventy-eight percent of all participants reported wanting to know the cause of their miscarriage, even if no intervention could have prevented it from occurring. Disclosures of miscarriages by public figures assuaged feelings of isolation for 28% of respondents. Level of education and gender had a significant effect on perceptions and understanding of miscarriage. CONCLUSION: Respondents to our survey erroneously believed that miscarriage is a rare complication of pregnancy, with the majority believing that it occurred in 5% or less of all pregnancies. There were also widespread misconceptions about causes of miscarriage. Those who had experienced a miscarriage frequently felt guilty, isolated, and alone. Identifying a potential cause of the miscarriage may have an effect on patients' psychological and emotional responses. LEVEL OF EVIDENCE: II Abstract : Widespread misperceptions exist as to the incidence and causes of miscarriage in the United States.Supplemental Digital Content is Available in the Text.